Restrictive measures of a criminal law nature in the system of legal regulation of prevention and to combat domestic violence - Oliinychenko Аngelina (Problems of legality, 2021)
The article is devoted to the study of the system of state measures applied to persons, who are suspected, accused of committing or having committed domestic violence, as well as determining the place of restrictive measures of a criminal law nature in the proposed system. For this purpose, it is necessary to conduct an analysis of the legislative regulation of state measures applicable to persons suspected of committing or having committed domestic violence at all levels of №rmative legal regulation; to delimitate the terms “restrictive measure”, “precautionary measure”, “restrictive prescription” and “temporary prohibition injunction” and to analyse the expediency of the new term “security measures” proposed by the draft of the new Criminal Code of Ukraine. The result of the conducted study is an analysis of the existing state measures to combat domestic violence in order to form a system of special measures to combat domestic violence, as well as examination of the issue concerning the place of restrictive measures of a criminal law nature applicable to persons having committed domestic violence. So, today, the system of special measures to combat domestic violence consists of types of measures to temporarily restrict the rights and obligations of the perpetrator who committed domestic violence, as well as to a person suspected, accused or committed a criminal offense related to domestic violence. The types of such measures are taking the offender into preventive registration and carrying out preventive work with him; referral of the offender to the offender program; a temporary injunction; a restrictive prescription of a civil nature a restrictive measure of a criminal procedure nature applicable to persons suspected or accused of committing domestic violence; and a restrictive measure of a criminal nature nature applicable to persons who have committed domestic violence having different preconditions, grounds , subjects and the term of appointment, but have the sole intention of protecting persons suffering from domestic violence.